(untitled) (Al-Qamar, 2022)
The study begins with the assumption that metaphors are widely used in the Quran. The Tafsir Al-Taḥrīr wa al-Tanvīr has special importance among all the Tafasirs due to its latest rhetorical analysis of the Quran. Metaphors have the essential elements of interest which need thorough investigation with special reference to Tafsir Ibn ʻĀshūr and his approach in the presentation of Quranic metaphors. The purpose of the study is to focus on the influence of metaphors on the meaning of verses of Quran in light of the Tafsir. The research also makes effort to link the modern scientific approach of rhetorical study with the approach of Shaykh Muhammad Al- Ibn ʻĀshūr. This Tafsir is of great importance for the researchers in terms of its analysis of metaphorical images and its kinds. The use of metaphors makes it easy to convey the required meaning(s) to the mankind. The research also studies the similarities and differences in the use of metaphorical images in Tafsir Ibn ʻĀshūr in comparison with previous rhetorical Tafasirs. The study also highlights the most rhetorical kinds of metaphors and its importance with special reference to Tafsir Ibn ʻĀshūr.